Bulk Segregant Analysis for the Identification of Shoot Fly Resistance Linked Molecular Marker in Sorghum [Sorghum bicolor (L.) Moench] - Solanki, Riteshkumar Satyanarayan; Gami, R. A.; Tiwari, K. K.; Patel, R. N.; Parmar, L. D.; Patel, P. S. (International Journal of Bio-resource and Stress Management, 2023)
Sorghum (Sorghum bicolor (L.) Moench) is one of the most important crops in the semi-arid regions of the world. One of the important biotic constraints to sorghum production in India is the shoot fly which attacks sorghum at the seedling stage. The study was undertaken during 2021–22 at the Centre for Millets Research, Sardarkrushinagar Dantiwada Agricultural University, Deesa, Gujarat, India to assess linked molecular markers for sorghum shoot fly resistance using the bulk segregant analysis (BSA) method with simple sequence repeat (SSR) marker from developed F2 mapping population with two genetically diverse parental lines, SWARNA (susceptible to shoot fly) and IS 18551 (resistant to shoot fly). Sixty-five SSRs primers pair were used for the parental polymorphism survey using two contrasting parents to detect the primers exhibiting polymorphism. Eight out of sixty-five primers showed polymorphism (12.30%) between two contrasting parental lines in sorghum. Two out of eight polymorphic SSRs primer pairs i.e., Xtxp 67 and Xgap 88 were found polymorphic between resistance and susceptibility in parents and bulks and thus reported to be putatively linked with shoot fly. Bulk segregant analysis (BSA) was extended to identify the traits controlled by minor genes with additive effects, which increased the power and efficiency of this molecular technique to construct genetic map in the sorghum crop improvement program. The identified SSRs markers i.e., Xtxp 67 and Xgap 88 might be useful to screen resistance for shoot fly infestation in future sorghum improvement program.